Dr. Martin Luther King Jr. Library - Tim Cech:::Photographer:::::::::::: (San Jose, California, 2023)
Facing the front doors of the Dr. Martin Luther King Jr. Library at San Fernando and 4th St. San Jose, Ca. The Martha Heasley Cox Center for Steinbeck Studies is on the 5th floor.